(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Myocardial infarction is a major cause of morbidity and mortality globally, profoundly affecting patients’ physical and psychological well-being. While survival rates have improved due to advanced acute interventions, long-term recovery heavily relies on effective cardiac rehabilitation. This study aims to evaluate the prognostic value of comprehensive rehabilitation programs on the quality of life of patients following a myocardial infarction. A prospective, randomized clinical trial was conducted involving 112 patients. Participants were divided into a main group (n=56) receiving a structured 12-week comprehensive cardiac rehabilitation program, and a control group (n=56) receiving standard outpatient care. Quality of life was assessed using the SF-36 Health Survey at baseline and after 6 months. Statistical analyses included Student’s t-test and chi-square tests (p < 0.05). After 6 months, the main group demonstrated significant improvements in physical functioning (74.2 ± 3.4 vs. 59.5 ± 4.1, p < 0.01) and mental health (71.8 ± 3.6 vs. 55.4 ± 4.2, p < 0.01) compared to the control group. Furthermore, the absolute risk reduction for early hospital readmission was 14.2% (95% CI: 8.5 - 19.9). In conclusion, the implementation of a systematic, multidisciplinary cardiac rehabilitation program significantly enhances both the physical and psycho-emotional components of quality of life in post-myocardial infarction patients, emphasizing the critical need for its integration into primary healthcare protocols.